A research on calculation of cost of pistachio production in Sanliurfa province - Paksoy S. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
In this research, the cost of pistachio production was calculated in farms in Center town, Bozova and Birecik town of Sanliurfa province. The research included 1996-1997 production period.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)